RETANNING EFFECT ON WATER REPELLENCY OF UPHOLSTERY LEATHER - Irieka Widiya Permata; Mustafidah Udkhiyati; R.L.M.S. Ari Wibowo (Politek ATK Yogyakarta Press, 2024)
Water repellent properties in upholstery leather is required to increase its durability. In this study, the effect of various retanning materials to the water repellent properties of upholstery leather is identified. The raw material used is IV quality of wet blue cow leather. The treatment is divided into 3 formulas, they are control using vegetable retanning materials such as mimosa, chestnut and tara; treatment 1 using vegetable (mimosa and chestnut), syntan tanning agent (white syntan/Basyntan DLE) and melamine resin (Eurosintan M)); and treatment 2 using syntan (white syntan/Basyntan DLE and softening syntan/Sertan BSF) and resin (melamine resin/Eurosintan M and acrylic resin/Retingan R7). Water absorption, tensile strength and elongation is carried out to test the effect. Based on the test results, it is showed that the treatment 2 produces upholstery leather with the highest water repellent properties with a water absorption test result of 24.75%. The results of the tensile strength and elongation tests produced in treatment 2 also complied with SNI 06-0779-1989 with values of 239.59 kg/cm2 and 75.27%, respectively.